MENINGKATKAN KEMAMPUAN BERPIKIR KREATIF SISWA MELALUIMODEL PEMBELAJARAN DISCOVERY LEARNINGDI SDN 15 JAKE KUANTAN TENGAH - Fendita Zulayan (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2022)
This article is a study description of classroom action research that is focused on the improvement of students' creative thinking skills. The study was conducted at SDN 15 Jake Kuantan Tengah in Kuantan Singingi. The study also involved 28 elementary students in grade VI, which consisted of 10 male students and 18 female students. The method used was descriptive-quantitative. The result of the study showed that after the application of learning with the discovery learning model, students' creative thinking skills increased. It is proven from the data analysis result of students' creative thinking skills. The percentage of students who complete the pre-cycle before being given action was 46.5%. Subsequently, in cycle I, it was found that the percentage of students who completed the test was 64.3%. In addition, in cycle II, the percentage was significantly 92.9%. Thus, it could be concluded that the application of the discovery learning model could increase the creative thinking skills of sixth-grade students at SDN 15 Jake Kuantan Tengah in Kuantan Singingi.